Sinoatrial Node Structure, Mechanics, Electrophysiology and the Chronotropic Response to Stretch in Rabbit and Mouse - MacDonald, Eilidh A.; Madl, Josef; Greiner, Joachim; Ramadan, Ahmed F.; Wells, Sarah M.; Torrente, Angelo G.; Kohl, Peter; Rog-Zielinska, Eva A.; Quinn, T. Alexander (Frontiers in Physiology, 2020)
The rhythmic electrical activity of the heart’s natural pacemaker, the sinoatrial node (SAN), determines cardiac beating rate (BR). SAN electrical activity is tightly controlled by multiple factors, including tissue stretch, which may contribute to adaptation of BR to changes in venous return. In most animals, including human, there is a robust increase in BR when the SAN is stretched. However, the chronotropic response to sustained stretch differs in mouse SAN, where it causes variable responses, including decreased BR. The reasons for this species difference are unclear. They are thought to relate to dissimilarities in SAN electrophysiology (particularly action potential morphology) between mouse and other species, and to how these interact with sub-cellular stretch-activated mechanisms. Furthermore, species-related differences in structural and mechanical properties of the SAN may influence the chronotropic response to SAN stretch. Here we assess: (i) how the BR response to sustained stretch of rabbit and mouse isolated SAN relates to tissue stiffness; (ii) whether structural differences could account for observed differences in BR responsiveness to stretch; and (iii) whether pharmacological modification of mouse SAN electrophysiology alters stretch-induced chronotropy. We found disparities in the relationship between SAN stiffness and the magnitude of the chronotropic response to stretch between rabbit and mouse, along with differences in SAN collagen structure, alignment, and changes with stretch. We further observed that pharmacological modification to prolong mouse SAN action potential plateau duration rectified the direction of BR changes during sustained stretch, resulting in a positive chronotropic response akin to that of other species. Overall, our results suggest that structural, mechanical, and background electrophysiological properties of the SAN influence the chronotropic response to stretch. Improved insight into the biophysical determinants of stretch effects on SAN pacemaking is essential for a comprehensive understanding of SAN regulation, with important implications for studies of SAN physiology and its dysfunction, such as in the aging and fibrotic heart.